An organizational capacity model for Portuguese wine cooperatives - Souza, Maria de Fátima Arruda (2018)
The purpose of this research is to develop a model of organizational capacity that can potentially lead wine cooperatives to achieve success, exploring the factors in the environment that affect their performance and present preliminary criteria to evaluate organizational capacity based on the model. Cooperatives are organizations with particular characteristics. Apart from having sharing cooperative principles and values, there is a dual nature to their purpose that has been noted in the literature. Cooperatives have both an economic and a social dimension: they are simultaneously a business and non-profit driven organizations owned by their members and controlled by them democratically. The aim of cooperatives is to maximise members’ service and satisfaction. Financial indicators alone are not suitable to assess cooperatives’ performance since they are not for-profit organization. So, the construct of organizational capacity, developed to assess the potential of non-profit organizations (NPO) to achieve their goals, was adapted to wine cooperatives in Portugal. Although there are models of organizational capacity for NPO, they do not fit the reality of cooperatives mainly because of their economic role. Cooperatives are also economically oriented businesses. A grounded theory approach was adopted for this research, which is a qualitative methodology that intends to systematically obtain and analyse data in social research to generate theory. Cooperatives were selected through theoretical sampling, aiming to reach cooperatives that could represent the diversity of the universe of 67 wine cooperatives in Portugal in 2015. Twenty-three people (members and managers) were interviewed in 19 wine cooperatives and unions in different regions of the country. The model of organizational capacity in the environment of wine cooperatives was developed taking into account the categories that emerged from data. The model provides a systemic view of the wine cooperative environment and has three sets of categories: members, environmental factors and the cooperative itself. The two categories that compose this last set are cooperative identity and organizational capacity. The core category in the model of organizational capacity in wine cooperatives is management because it is the required ability of managers that allows them to coordinate the environmental factors and other capacities of the cooperative.